DACH. - Staes, Jeroen; Van Cauteren, Philippe; Paschalidis, Iris (Koksijde : Ten Bogaerde : S.M.A.K., 2021)
Oberhuber, Oswald ; Morellet, François ; Flavin, Dan ; Rabinowitch, Royden ; Bogaert, André ; De Keyser, Raoul ; Roth, Dieter ; Heyvaert, René ; Panamarenko ; Beuys, Joseph ; Long, Richard ; Van Snick, Philippe ; Fabro, Luciano ; Fritsch, Katharina ; Vermeiren, Didier ; Vercruysse, Jan ; Visch, Henk ; Bijl, Guillaume ; McCracken, John ; West, Franz ; Serra, Richard ; François, Michel ; Ryslavy, Kurt ; Meireles, Cildo ; Leonard, Zoe ; 't Jolle, Sven ; Garutti, Alberto ; Goldstein, Zvi ; Schouten, Marien ; Tahon, Johan ; Downsbrough, Peter ; Houseago, Thomas ; De Cordier, Thierry ; Rist, Pipilotti ; Owens, Laura ; Brey, Ricardo ; Fainaru, Belu-Simion ; Hultén, Sofia ; Tordoir, Narcisse ; Geyskens, Vincent ; Wilkes, Cathy ; Pasaiko, Oksana ; Ortmeyer, Sarah ; Cloquet, Marie ; Weinberger, Lois ; Atta Sabri, Salam ; Prieto, Wilfredo ; Storch, Tove ; Baghramian, Nairy ; Borremans, Michaël ; Sailstorfer, Michael ; Wilkinson, Monday ; Shust, Jura ; Canell, Nina ; Katambayi Mukendi, Jean ; Nashashibi/Skaer ; Van Dijck, Hannelore ; Escoval, Joana ; Aydoslu, Leyla ; Bartolini, Massimo ; Matloga, Neo ; Lloyd Corporation ; Littwitz, Ella ; Benaouisse, Ben ; Tuttle, Richard ; Tinguely, Jean
Dach, Kunstencentrum Ten Bogaerde, Koksijde, 5 juni tot 14 november 2021
boek